Optical film, polarizing plate, and image display device
By using a polymerizable compound with side-chain groups localized on the substrate side in the alignment film, the optical film achieves easy peeling with controlled force and maintains adhesion, addressing the challenge of high peeling force in optical films.
Patent Information
- Application Number
- CN202380037913.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-03-02
- Filing Date
- 2023-04-14
- Publication Date
- 2024-12-13
AI Technical Summary
The peeling force of substrates in optical films is high, making it difficult to peel off the substrate while ensuring sufficient adhesion between the substrate and the alignment film during operations other than peeling.
Incorporating a specific compound with polymerizable groups on side chains in the alignment film, localized on the substrate side, allows for easy peeling of the substrate with maintained adhesion through secondary ion intensity distribution.
Facilitates easy peeling of the substrate with controlled peeling force (0.03 to 0.40 N/25 mm) and ensures strong adhesion between the substrate and alignment film during operations.
Smart Images

Figure BDA0005114115940000071 
Figure BDA0005114115940000081 
Figure BDA0005114115940000091
Abstract
Description
Technical Field
[0001] The invention relates to an optical film, a polarizing plate and an image display device. Background Art
[0002] Optical films such as optical compensation sheets and retardation films are used in various image display devices from the viewpoints of eliminating image coloration and widening the viewing angle.
[0003] As the optical film, a stretched birefringent film is used. However, in recent years, it has been proposed to use an optically anisotropic layer (liquid crystal layer) using a liquid crystal compound instead of the stretched birefringent film.
[0004] In an image display device (for example, a liquid crystal display device), a linear polarizer or a circular polarizer is used to control optical rotation or birefringence during display.
[0005] Conventionally, iodine has been widely used as a dichroic substance in these polarizers, but research has also been conducted on light absorption anisotropic layers (liquid crystal layers) that use dichroic substances instead of iodine and utilize the alignment of liquid crystal compounds.
[0006] It is known that such a liquid crystal layer is formed by providing an alignment film on a substrate (support) on which the liquid crystal layer is formed in order to align a liquid crystal compound.
[0007] For example, Patent Document 1 describes a method including a support, a photo-alignment film formed using a composition containing a predetermined copolymer, and a light absorption anisotropic layer formed using a composition containing a liquid crystal compound and a dichroic substance in this order.
[0008] Previous technical literature
[0009] Patent Literature
[0010] Patent Document 1: International Publication No. 2020 / 179864 Summary of the invention
[0011] Technical issues to be solved by the invention
[0012] The present inventors have studied the optical film having a substrate, an alignment film, and a liquid crystal layer in this order as described in Patent Document 1, etc., and have found that the peeling force is high and sometimes it is difficult to peel off the substrate when the substrate is to be peeled off from the viewpoint of thinning or transfer.
[0013] The inventors have found that the peeling force of the substrate can be reduced by adjusting the coating method or formulation of the alignment film, but have found that the substrate may be peeled off unexpectedly when other components are peeled off based on the peeling force of the substrate.
[0014] Therefore, an object of the present invention is to provide an optical film, a polarizing plate, and an image display device that can easily peel off a substrate and can sufficiently ensure adhesion between the substrate and an alignment film in operations other than peeling off the substrate.
[0015] Means for solving technical problems
[0016] As a result of intensive research conducted by the inventors to achieve the above-mentioned problems, the inventors discovered the following and completed the present invention: in an optical film having a substrate, an orientation film and a liquid crystal layer in sequence, at least one specific compound selected from the group consisting of polymerizable polymers having polymerizable groups on side chains and polymers thereof is contained, and an orientation film is used in which the maximum value of the secondary ion intensity originating from the specific compound exists in a region from the surface of the substrate side to a thickness position of 100 nm, thereby allowing the substrate to be easily peeled off when peeling off, and sufficient adhesion between the substrate and the orientation film can be ensured during operations other than peeling off the substrate.
[0017] That is, the present inventors have found that the above-mentioned problems can be solved by the following configuration.
[0018] [1] An optical film comprising, in this order, a substrate, an alignment film, and a liquid crystal layer,
[0019] The alignment film contains at least one specific compound selected from the group consisting of polymerizable macromolecules having a polymerizable group on a side chain and polymers of polymerizable macromolecules.
[0020] When the intensity of secondary ions originating from a specific compound in the orientation film is measured by time-of-flight secondary ion mass spectrometry while irradiating an ion beam from the surface of the orientation film on the liquid crystal layer side toward the surface on the substrate side, the maximum value of the secondary ion intensity originating from the specific compound exists in the region from the surface on the substrate side to the thickness position of 100 nm.
[0021] [2] The optical film according to [1], wherein
[0022] The specific compound is a polymer of a polymerizable macromolecular compound.
[0023] [3] The optical film according to [1] or [2], wherein
[0024] The alignment film is a photo-alignment film.
[0025] [4] The optical film according to [3], wherein
[0026] The photo-alignment film is an alignment film formed using an alignment film-forming composition containing a polymerizable polymer and a photo-alignment compound. The polymerizable polymer has a radical polymerizable group, and the photo-alignment compound has a cation polymerizable group.
[0027] [5] The optical film according to [4], wherein
[0028] The alignment film forming composition contains a polymerization initiator.
[0029] [6] The optical film according to [5], wherein
[0030] The polymerization initiator is a photoradical polymerization initiator.
[0031] [7] The optical film according to any one of [1] to [6], wherein
[0032] The content of the specific compound is 0.2 to 20% by mass based on the mass of the alignment film.
[0033] [8] The optical film according to any one of [1] to [7], wherein
[0034] The liquid crystal layer contains a dichroic substance.
[0035] [9] The optical film according to any one of [1] to [8], wherein
[0036] The peeling force when peeling the substrate from the oriented film was 0.03 to 0.40 N / 25 mm.
[0037]
[10] The optical film according to any one of [1] to [9], wherein
[0038] The absolute value of the difference between the SP value of the polymer and the SP value of the substrate is 1.7 MPa. 1 / 2 the following.
[0039]
[11] The optical film according to any one of [1] to
[10] , wherein
[0040] The weight average molecular weight of the polymerizable polymer is 5,000 to 100,000.
[0041]
[12] The optical film according to any one of [1] to
[11] , wherein
[0042] The polymerizable group is an acryloyl group or a methacryloyl group.
[0043]
[13] A polarizing plate comprising the optical film according to any one of [1] to
[12] .
[0044]
[14] An image display device comprising the optical film according to any one of [1] to
[12] .
[0045]
[15] An image display device comprising the polarizing plate described in
[13] .
[0046] Effects of the Invention
[0047] According to the present invention, it is possible to provide an optical film, a polarizing plate, and an image display device that can easily peel off the substrate and can sufficiently ensure adhesion between the substrate and the alignment film in operations other than peeling the substrate. DETAILED DESCRIPTION
[0048] Hereinafter, the present invention will be described in detail.
[0049] Although the description of the constituent elements described below may be based on representative embodiments of the present invention, the present invention is not limited to such embodiments.
[0050] In addition, in this specification, the numerical range expressed using "to" means a range including the numerical values described before and after "to" as the lower limit and the upper limit.
[0051] In addition, in this specification, regarding each component, one substance corresponding to each component can be used alone, or two or more substances can be used simultaneously. Here, regarding each component, when two or more substances are used simultaneously, the content of the component, unless otherwise specified, refers to the total content of the substances used simultaneously.
[0052] In addition, in this specification, "(meth)acrylic acid" is a mark which represents "acrylic acid" or "methacrylic acid".
[0053] In this specification, Re(λ) and Rth(λ) represent the in-plane retardation and the retardation in the thickness direction at a wavelength λ, respectively. In addition, unless otherwise specified, the wavelength λ is 550 nm.
[0054] In this specification, Re(λ) and Rth(λ) are values measured at a wavelength λ using AxoScan (manufactured by Axometrics).
[0055] Specifically, by using AxoScan to input the average refractive index ((nx+ny+nz) / 3) and film thickness (d (μm)), the following is calculated:
[0056] In-plane slow axis direction (°)
[0057] Re(λ)=R0(λ)
[0058] Rth(λ)=((nx+ny) / 2-nz)×d.
[0059] In addition, R0(λ) is expressed as a numerical value calculated by AxoScan, but refers to Re(λ).
[0060] [Optical film]
[0061] The optical film of the present invention includes a substrate, an alignment film, and a liquid crystal layer in this order.
[0062] Furthermore, the alignment film contains at least one specific compound selected from the group consisting of polymerizable macromolecules having a polymerizable group on a side chain and polymers of the polymerizable macromolecules.
[0063] Moreover, when the intensity of secondary ions originating from a specific compound in the alignment film is measured by time-of-flight secondary ion mass spectrometry (TOF-SIMS) while irradiating an ion beam from the surface of the liquid crystal layer side of the alignment film toward the surface on the substrate side, the maximum value of the secondary ion intensity originating from the specific compound exists in the region from the surface on the substrate side to the thickness position of 100 nm.
[0064] In addition, in the following description, the region where the maximum value of the secondary ion intensity originating from the specific compound exists in the thickness position from the surface of the substrate side to 100 nm is also referred to as "the specific compound is biased on the substrate side". As a method for confirming that the specific compound is biased on the substrate side, it can be confirmed by the method described in the examples described later.
[0065] Furthermore, when the alignment film contains two or more specific compounds, at least one specific compound may be localized on the substrate side.
[0066] In the present invention, as described above, in an optical film having a substrate, an orientation film and a liquid crystal layer in sequence, by using an orientation film with a specific compound biased on the substrate side, the substrate can be easily peeled off when peeling off the substrate, and the close adhesion between the substrate and the orientation film can be fully ensured during operations other than peeling off the substrate.
[0067] The reason why this effect is achieved is not clear in detail, but the present inventors speculate as follows.
[0068] That is, the inventors of the present invention believe that, when forming an optical film, a specific compound that is biased toward the substrate side in the oriented film suppresses anchoring caused by other components and can be cross-linked with the substrate surface as needed, thereby being able to adjust the peeling force of the substrate within an appropriate range. Therefore, the substrate can be easily peeled off when peeling off, and the close adhesion between the substrate and the oriented film can be fully ensured during operations other than peeling off the substrate.
[0069] In the present invention, from the perspective of the fact that the substrate can be easily peeled off when peeling off the substrate and the adhesion between the substrate and the oriented film can be more fully ensured during operations other than peeling off the substrate (hereinafter referred to as "the reason why the effect of the present invention is more excellent"), the peeling force when peeling the substrate from the oriented film (hereinafter also referred to as "the peeling force of the substrate") is preferably 0.03 to 0.40 N / 25 mm, and more preferably 0.05 to 0.35 N / 25 mm.
[0070] Here, the peeling force of the substrate refers to the peeling force when an optical film having a substrate, an orientation film and a liquid crystal layer in sequence is cut into 150 mm×25 mm, the surface of the optical film opposite to the substrate is fixed to a workbench using an adhesive with a thickness of 15 μm (Opteria D692 manufactured by LINTEC Corporation.), and the substrate is peeled off in a 180° direction at a speed of 5 m / min under an environment of 25°C. The peeling force can be measured by a digital dynamometer RZ-1 manufactured by AIKOH ENGINEERING Co., LTD.
[0071] 〔Base material〕
[0072] The substrate of the optical film of the present invention is not particularly limited, and a known substrate can be used. In particular, a transparent substrate is preferably used. In addition, a transparent substrate refers to a substrate with a visible light transmittance of 60% or more, preferably 80% or more, and more preferably 90% or more.
[0073] Examples of such a substrate include a glass substrate and a polymer film.
[0074] Examples of materials for the polymer film include cellulose polymers; acrylic polymers having acrylate polymers such as polymethyl methacrylate and lactone ring-containing polymers; thermoplastic norbornene polymers; polycarbonate polymers; polyester polymers such as polyethylene terephthalate and polyethylene naphthalate; styrene polymers such as polystyrene and acrylonitrile-styrene copolymers; polyolefin polymers such as polyethylene, polypropylene and ethylene-propylene copolymers; vinyl chloride polymers; amide polymers such as nylon and aromatic polyamide; imide polymers; sulfone polymers; polyethersulfone polymers; polyetheretherketone polymers; polyphenylene sulfide polymers; vinylidene chloride polymers; vinyl alcohol polymers; vinyl butyral polymers; aromatic ester polymers; polyoxymethylene polymers; epoxy polymers; or polymers obtained by mixing these polymers.
[0075] Among these, polymer films using cellulose-based polymers, particularly cellulose acylate-based polymers (cellulose acylate-based films) are preferred.
[0076] The thickness of the substrate is not particularly limited, but is preferably 10 to 100 μm, and more preferably 30 to 80 μm.
[0077] 〔Oriented film〕
[0078] As described above, the alignment film of the optical film of the present invention contains at least one specific compound selected from the group consisting of polymerizable macromolecules having polymerizable groups in side chains and polymers of the polymerizable macromolecules, and the specific compound is localized on the substrate side.
[0079] <Specified compounds>
[0080] Regarding the polymerizable polymer as one embodiment of the specific compound, the polymerizable group on the side chain is not particularly limited, but is preferably a polymerizable group capable of radical polymerization or cation polymerization.
[0081] Here, as a radical polymerizable group (photo-crosslinkable group), a (meth)acryloyl group, an acrylamide group, a vinyl group, a styryl group, an allyl group, etc. are mentioned, for example.
[0082] Examples of the cationically polymerizable group (thermal crosslinkable group) include a vinyl ether group, an oxirane group, and an oxetane group.
[0083] In the present invention, the polymerizable group is preferably a (meth)acryloyl group because the effects of the present invention are more excellent.
[0084] Furthermore, in the present invention, the polymerizable polymer preferably does not have a photo-alignment group described in the photo-alignment compound described later.
[0085] The structure of the main chain of the above-mentioned polymerizable polymer is not particularly limited, and known structures can be cited, for example, preferably a skeleton selected from the group including a (meth)acrylic skeleton, a styrene skeleton, a siloxane skeleton, a cycloolefin skeleton, a methylpentene skeleton, an amide skeleton and an aromatic ester skeleton.
[0086] Among these, a skeleton selected from the group consisting of a (meth)acrylic skeleton, a siloxane skeleton, and a cycloolefin skeleton is more preferred, and a (meth)acrylic skeleton is further preferred.
[0087] In the present invention, the polymerizable polymer preferably has a repeating unit represented by the following formula (1) because the effects of the present invention are more excellent.
[0088] [Chemical formula 1]
[0089]
[0090] R 1It represents a hydrogen atom or an alkyl group having 1 to 4 carbon atoms.
[0091] L 1 represents a single bond or an n+1 valent linking group. For example, when n is 1, L 1 represents a divalent linking group, and when n is 2, L 1 represents a trivalent linking group. 1 In the case of a single bond, n represents 1.
[0092] Examples of the divalent linking group include a divalent aliphatic hydrocarbon group (e.g., an alkylene group) which may have a substituent, an arylene group which may have a substituent, a heteroarylene group which may have a substituent, -O-, -CO-, -NH-, or a group formed by combining two or more of these. Examples of the group formed by combining two or more of these include a divalent aliphatic hydrocarbon group which may have a -CO-O- substituent, a divalent aliphatic hydrocarbon group which may have -O-, -CO-O- substituents, a divalent aliphatic hydrocarbon group which may have -NH- and -CO-O- substituents, and a divalent aliphatic hydrocarbon group which may have a -O-CO-NH- substituent.
[0093] Examples of the trivalent linking group include a trivalent aliphatic hydrocarbon group which may have a substituent, a trivalent aromatic group which may have a substituent, a nitrogen atom (>N-), and a group formed by combining these groups with the above-mentioned divalent linking group.
[0094] P 1 represents a polymerizable group, and examples of the polymerizable group include polymerizable groups capable of the above-mentioned radical polymerization or cationic polymerization.
[0095] n represents an integer greater than or equal to 1. Among them, n is preferably 1 or 2, and more preferably 1, because the effects of the present invention are more excellent.
[0096] The content of the repeating unit represented by the above formula (1) is preferably 20% by mass or more, more preferably 30% by mass or more, and further preferably 50% by mass or more relative to the total mass of all repeating units of the polymerizable polymer. The upper limit is not particularly limited, but 100% by mass can be cited, and most are 95% by mass or less.
[0097] Examples of the repeating unit represented by the formula (1) include the repeating units shown in Table 1 below. These may be used alone or in combination of two or more.
[0098] [Table 1]
[0099]
[0100] The polymerizable polymer may have other repeating units in addition to the repeating unit represented by the above formula (1).
[0101] As other repeating units, from the reason that the effects of the present invention are more excellent, a repeating unit represented by the following formula (2) can be mentioned.
[0102] [Chemical formula 2]
[0103]
[0104] R 2 It represents a hydrogen atom or an alkyl group having 1 to 4 carbon atoms.
[0105] L 2 represents a single bond or a divalent linking group. Examples of the divalent linking group include L 1 The groups exemplified as divalent linking groups are represented by:
[0106] R 3 represents an aliphatic hydrocarbon group which may have a substituent, or one or more -CH 2 - A group substituted by -O-, -S-, -NH-, -N(Q)- or -CO-. Q represents a substituent.
[0107] The number of carbon atoms contained in the aliphatic hydrocarbon group is not particularly limited, but is preferably 1-20, and more preferably 1-10.
[0108] The aliphatic hydrocarbon group may be linear or branched, and may have a cyclic structure.
[0109] The substituent is not particularly limited, but examples thereof include alkyl, alkoxy, alkyl-substituted alkoxy, cyclic alkyl, aryl (eg, phenyl and naphthyl), cyano, amino, nitro, alkylcarbonyl, sulfo and hydroxyl groups.
[0110] When the polymerizable polymer contains other repeating units, the content of the other repeating units (for example, the repeating units represented by the above formula (2)) is not particularly limited, but is preferably 80% by mass or less, more preferably 50% by mass or less, and further preferably 30% by mass or less relative to the total mass of all repeating units of the polymerizable polymer. The lower limit is not particularly limited, but can be 5% by mass or more.
[0111] Examples of other repeating units include repeating units shown in Table 2 below. These may be used alone or in combination of two or more.
[0112] [Table 2]
[0113]
[0114] In the present invention, it is easy to adjust the peeling force of the substrate within the range of 0.05 to 0.35 N / 25 mm, and as a result, the effect of the present invention becomes more excellent. Therefore, the absolute value of the difference between the SP value of the polymerizable polymer and the SP value of the substrate is preferably 1.7 MPa. 1 / 2 The lower limit is not particularly limited, but 0 is an example.
[0115] Here, the SP value refers to the non-dispersion force component δa of the SP value calculated by the method of Hoy et al. (see Van Krevelen, DW., “Properties of Polymers (ED. 3)”, published by Elseville (1990)).
[0116] That is, the δa value can be calculated by the following formula (X) using the three-dimensional SP values (δd, δp, δh) calculated by the method of Hoy et al.
[0117] δa=(δp 2 +δh 2 ) 0.5 Formula (X)
[0118] According to the method of Hoy et al., the values of δd, δp, and δh can be calculated from the chemical structural formula of the compound to be determined.
[0119] In the case of a copolymer composed of a plurality of repeating units, the square value of the three-dimensional SP value (δd 2 ,δp 2 ,δh 2 ) multiplied by the volume fraction of each repeating unit and summed to calculate the square value of the three-dimensional SP value of the copolymer (δd 2 ,δp 2 ,δh 2 ), and by substituting the square value into the above formula (X), the δa value of the copolymer can be calculated.
[0120] In the present invention, the weight average molecular weight of the polymerizable polymer is preferably 5,000 to 100,000, more preferably 7,500 to 50,000, because the effects of the present invention are more excellent.
[0121] Here, the weight average molecular weight is a value measured by gel permeation chromatography (GPC) under the conditions shown below.
[0122] Solvent (eluent): THF (tetrahydrofuran)
[0123] Device name: TOSOH HLC-8320GPC
[0124] Column: 3 TOSOH TSKgel Super HZM-H (4.6 mm x 15 cm) connected and used
[0125] Column temperature: 40℃
[0126] Sample concentration: 0.1 mass%
[0127] Flow rate: 1.0ml / min
[0128] Calibration curve: Calibration curve obtained using 7 samples of TSK standard polystyrene Mw=2800000 to 1050 (Mw / Mn=1.03 to 1.06) manufactured by TOSOH CORPORATION
[0129] In the present invention, the specific compound is preferably a polymer of the above-mentioned polymerizable polymer, that is, a crosslinked product of the above-mentioned polymerizable polymer, because the effects of the present invention are more excellent.
[0130] In the present invention, the content of the specific compound is preferably 0.2 to 20 mass %, more preferably 0.3 to 10 mass %, and further preferably 0.4 to 8 mass % based on the mass of the alignment film in order to improve the degree of alignment of the liquid crystal layer described later.
[0131] The thickness of the alignment film is not particularly limited, but is preferably 0.1 to 10 μm, and more preferably 0.5 to 5 μm.
[0132] The alignment film of the optical film of the present invention is not particularly limited except that the above-mentioned specific compound is biased on the substrate side. As long as the liquid crystal layer described later can be in a desired alignment state, it can be a rubbing treatment alignment film formed by rubbing treatment or a photo alignment film formed by light irradiation. Among them, the photo alignment film is preferred.
[0133] Furthermore, the orientation film possessed by the optical film of the present invention makes it easy to change the direction of the orientation restriction force according to the purpose, so that the liquid crystal orientation direction of the liquid crystal layer described later can be freely controlled. For example, if it is a light orientation treatment, the vibration direction of the polarized light during polarized exposure is changed, and if it is a friction treatment, the direction of the friction is changed, thereby making it easy to change the direction of the orientation restriction force. In particular, in the case of roll-to-roll manufacturing, the direction of the orientation restriction force relative to the length direction of the long strip orientation film can be easily selected in any direction of 0° to 90°. Moreover, in the case of assuming bonding with other components of the roll-to-roll method, the axis angle with other components can be changed according to the required use, and the manufacturing process can be optimized.
[0134] <Photo-alignment film>
[0135] As photo-alignment compounds used in the photo-alignment film formed by light irradiation, there are records in a plurality of documents, etc. In the present invention, as preferred examples, for example, azo compounds described in Japanese Patent Publication No. 2006-285197, Japanese Patent Publication No. 2007-76839, Japanese Patent Publication No. 2007-138138, Japanese Patent Publication No. 2007-94071, Japanese Patent Publication No. 2007-121721, Japanese Patent Publication No. 2007-140465, Japanese Patent Publication No. 2007-156439, Japanese Patent Publication No. 2007-133184, Japanese Patent Publication No. 2009-109831, Japanese Patent No. 3883848, and Japanese Patent No. 4151746 can be cited. Compounds, aromatic ester compounds described in Japanese Patent Publication No. 2002-229039, maleimide and / or alkenyl-substituted nadic imide compounds having photo-alignment units described in Japanese Patent Publication No. 2002-265541 and Japanese Patent Publication No. 2002-317013, photo-crosslinkable silane derivatives described in Japanese Patent No. 4205195 and Japanese Patent No. 4205198, photo-crosslinkable polyimides, polyamides or esters described in Japanese Patent Publication No. 2003-520878, Japanese Patent Publication No. 2004-529220 or Japanese Patent No. 4162850. More preferably, azo compounds, photo-crosslinkable polyimides, polyamides or esters.
[0136] Among these, as the photo-alignment compound, it is preferable to use a photosensitive compound having a photo-alignment group that undergoes at least one of dimerization and isomerization by the action of light.
[0137] In addition, as the photo-alignment group, for example, there can be mentioned a group having a cinnamic acid (cinnamoyl) structure (skeleton), a group having a coumarin structure (skeleton), a group having a chalcone structure (skeleton), a group having a benzophenone structure (skeleton), and a group having an anthracene structure (skeleton). Among these groups, a group having a cinnamoyl structure and a group having a coumarin structure are preferred, and a group having a cinnamoyl structure is more preferred.
[0138] Furthermore, the photosensitive compound having the above-mentioned photo-alignment group may further have a crosslinking group.
[0139] The crosslinkable group is preferably a thermal crosslinkable group that causes a curing reaction by heat or a photo crosslinkable group that causes a curing reaction by light, and may be a crosslinkable group having either a thermal crosslinkable group or a photo crosslinkable group.
[0140] Examples of the crosslinkable group include epoxy, oxetanyl, -NH-CH2 At least one of the group consisting of -OR (R represents a hydrogen atom or an alkyl group having 1 to 20 carbon atoms), a group having an ethylenically unsaturated double bond, and a blocked isocyanate group. Among them, an epoxy group, an oxetanyl group, and a group having an ethylenically unsaturated double bond are preferred.
[0141] In addition, a three-membered ring cyclic ether group is also called an epoxy group, and a four-membered ring cyclic ether group is also called an oxetanyl group.
[0142] Furthermore, specific examples of the group having an ethylenically unsaturated double bond include a vinyl group, an allyl group, a styryl group, an acryloyl group, and a methacryloyl group, and an acryloyl group or a methacryloyl group is preferred.
[0143] The photo-alignment film formed of the above-mentioned material is irradiated with linearly polarized light or non-polarized light to produce the photo-alignment film.
[0144] In this specification, "linearly polarized light irradiation" and "non-polarized light irradiation" are operations for causing a photoreaction in a photo-alignment material. The wavelength of the light used varies depending on the photo-alignment material used, and is not particularly limited as long as it is a wavelength required for the photoreaction. The peak wavelength of the light used for light irradiation is preferably 200nm to 700nm, and more preferably ultraviolet light with a peak wavelength of 400nm or less.
[0145] The light source used for light irradiation includes commonly used light sources, such as tungsten lamps, halogen lamps, xenon lamps, xenon flash lamps, mercury lamps, mercury-xenon lamps and carbon arc lamps, various lasers [for example, semiconductor lasers, helium-neon lasers, argon ion lasers, helium-cadmium lasers and YAG (yttrium aluminum garnet) lasers], light emitting diodes and cathode ray tubes, etc.
[0146] As a method of obtaining linearly polarized light, a method using a polarizing plate (e.g., an iodine polarizing plate, a dichroic pigment polarizing plate, and a wire grid polarizing plate), a method using a prism system element (e.g., a Glan-Thomson prism) or a reflective polarizer using the Brewster angle, or a method using light emitted from a laser light source having polarized light can be adopted. In addition, a filter or a wavelength conversion element can be used to selectively irradiate only light of a desired wavelength.
[0147] When the irradiated light is linearly polarized light, the method of irradiating the light from the upper surface or the back surface of the alignment film perpendicularly or obliquely relative to the alignment film surface is adopted. The incident angle of the light varies depending on the photo-alignment material, but is preferably 0 to 90° (perpendicular), preferably 40 to 90°.
[0148] In the case of non-polarized light, the alignment film is irradiated with non-polarized light from an oblique direction, and the incident angle is preferably 10 to 80°, more preferably 20 to 60°, and further preferably 30 to 50°.
[0149] The irradiation time is preferably 1 minute to 60 minutes, more preferably 1 minute to 10 minutes.
[0150] When patterning is required, a method of performing light irradiation using a photomask a number of times required for patterning or a method of writing a pattern by laser scanning can be adopted.
[0151] In the present invention, the photo-alignment film is preferably an alignment film formed using an alignment film-forming composition containing the above-mentioned polymerizable polymer and a photo-alignment compound (particularly, a photosensitive compound having a photo-alignment group).
[0152] Furthermore, the polymerizable compound preferably has a radical polymerizable group (photocrosslinkable group) as the polymerizable group, and the photo-alignment compound preferably has a cation polymerizable group (thermal crosslinkable group).
[0153] Furthermore, in the present invention, the alignment film-forming composition preferably contains a polymerization initiator.
[0154] The polymerization initiator is not particularly limited, and examples thereof include a photoradical polymerization initiator and a thermal cationic polymerization initiator, depending on the form of the polymerization reaction.
[0155] As the polymerization initiator, a photoradical polymerization initiator capable of initiating a polymerization reaction by ultraviolet irradiation is preferred.
[0156] Examples of the photoradical polymerization initiator include α-carbonyl compounds, acyloin ethers, α-hydrocarbon-substituted aromatic acyloin compounds, polynuclear quinone compounds, a combination of a triarylimidazole dimer and p-aminophenyl ketone, acridine and phenazine compounds, oxadiazole compounds, and acylphosphine oxide compounds.
[0157] When the alignment film forming composition contains a photoradical polymerization initiator, the content of the photoradical polymerization initiator is preferably 0.1 to 10% by mass, more preferably 1 to 5% by mass, based on the total solid content of the alignment film forming composition.
[0158] Furthermore, when the alignment film forming composition contains a thermal cationic polymerization initiator, the content of the thermal cationic polymerization initiator is preferably 1 to 30% by mass, more preferably 4 to 20% by mass, based on the total solid content of the alignment film forming composition.
[0159] In the present invention, the alignment film-forming composition may contain additives other than the above-mentioned components.
[0160] As other additives, for example, compounds added for the purpose of adjusting the refractive index of the alignment film can be cited. As such a compound, from the viewpoint of compatibility with the above-mentioned photo-alignment compound, a compound having a hydrophilic group and / or a (meth)acryloyloxy group is preferably added to a degree that does not significantly reduce the alignment ability. As the hydrophilic group, hydroxyl, carboxyl, sulfonic, amino, etc. can be cited.
[0161] In addition, the oriented film of the optical film of the present invention is preferably an oriented film having an average refractive index of 1.55 or more and 1.8 or less at a wavelength of 550 nm. From the perspective of improving anti-reflection performance, the refractive index difference with the liquid crystal layer (light absorption anisotropic layer) is preferably set to 0.1 or less, and more preferably set to 0.05 or less.
[0162] Furthermore, as other additives, for example, compounds added for the purpose of adjusting the elastic modulus of the orientation film can be cited. As such compounds, crosslinking agents, fillers, plasticizers, etc. can be cited. Among them, from the viewpoint of not reducing the orientation ability, a crosslinking agent is preferred. Moreover, the crosslinking group possessed by the crosslinking agent is preferably capable of reacting with the photo-orientation group possessed by the photosensitive compound. Moreover, the crosslinking agent also preferably has multiple crosslinking groups in one molecule. As preferred examples of crosslinking agents, for example, the compounds described in paragraphs
[0102] to
[0107] of International Publication No. 2022 / 071054 can be cited.
[0163] In addition, as other additives, for example, close contact improvers, surfactants, etc. Preferred examples of close contact improvers include reactive additives listed in paragraphs
[0123] to
[0129] of Japanese Patent Application Laid-Open No. 2019-91088.
[0164] Furthermore, in the present invention, the alignment film-forming composition preferably contains a solvent.
[0165] Examples of the solvent include ketones (e.g., acetone, 2-butanone, methyl isobutyl ketone, cyclopentanone, and cyclohexanone), ethers (e.g., dioxane and tetrahydrofuran), aliphatic hydrocarbons (e.g., hexane), alicyclic hydrocarbons (e.g., cyclohexane), aromatic hydrocarbons (e.g., toluene, xylene, and trimethylbenzene), halogenated carbons (e.g., dichloromethane, dichloroethane, dichlorobenzene, and chlorotoluene), esters (e.g., methyl acetate, ethyl acetate, and butyl acetate), water, alcohols (e.g., ethanol, isopropanol, butanol, and cyclohexanol), cellosolves (e.g., methyl cellosolve and ethyl cellosolve), cellosolve acetates, sulfoxides (e.g., dimethyl sulfoxide), and amides (e.g., dimethylformamide and dimethylacetamide).
[0166] One type of solvent may be used alone, or two or more types may be used simultaneously.
[0167] 〔Liquid crystal layer〕
[0168] The liquid crystal layer included in the optical film of the present invention is a layer in which the alignment state of the liquid crystal compound is fixed.
[0169] <Liquid crystal compounds>
[0170] As the liquid crystal compound, any of a high molecular weight liquid crystal compound and a low molecular weight liquid crystal compound can be used.
[0171] Here, the "polymer liquid crystal compound" refers to a liquid crystal compound having a repeating unit in its chemical structure.
[0172] Here, the "low-molecular liquid crystal compound" refers to a liquid crystal compound having no repeating unit in the chemical structure.
[0173] Examples of the polymer liquid crystal compound include the thermotropic liquid crystal polymer described in JP-A-2011-237513 and the polymer liquid crystal compound described in paragraphs
[0012] to
[0042] of WO 2018 / 199096.
[0174] Examples of the low-molecular liquid crystal compound include the liquid crystal compounds described in paragraphs
[0072] to
[0088] of JP-A-2013-228706, and among these, liquid crystal compounds showing smecticity are preferred.
[0175] Examples of such liquid crystal compounds include those described in paragraphs
[0019] to
[0140] of International Publication No. 2022 / 014340, and these descriptions are incorporated into this specification by reference.
[0176] The content of the liquid crystal compound is preferably 50 to 99% by mass, more preferably 75 to 90% by mass, based on the total mass of the liquid crystal layer.
[0177] <Dichroic substances>
[0178] In the present invention, from the viewpoint of making the liquid crystal layer function as a light absorption anisotropic layer, it is preferred that a dichroic substance is contained.
[0179] Here, the dichroic substance refers to a pigment whose light absorbance differs depending on the direction. The dichroic substance may or may not exhibit liquid crystallinity.
[0180] There is no particular limitation on dichroic substances, and examples thereof include visible light absorbing substances (dichroic pigments), luminescent substances (fluorescent substances, phosphorescent substances), ultraviolet absorbing substances, infrared absorbing substances, nonlinear optical substances, carbon nanotubes and inorganic substances (such as quantum rods), etc. Conventionally known dichroic substances (dichroic pigments) can be used.
[0181] Specifically, for example, paragraphs
[0067] to
[0071] of Japanese Patent Application Laid-Open No. 2013-228706, paragraphs
[0008] to
[0026] of Japanese Patent Application Laid-Open No. 2013-227532, paragraphs
[0008] to
[0015] of Japanese Patent Application Laid-Open No. 2013-209367, paragraphs
[0045] to
[0058] of Japanese Patent Application Laid-Open No. 2013-14883, paragraphs
[0012] to
[0029] of Japanese Patent Application Laid-Open No. 2013-109090, paragraphs
[0009] to
[0017] of Japanese Patent Application Laid-Open No. 2013-101328, and paragraphs
[0051] to
[0065] of Japanese Patent Application Laid-Open No. 2013-37353. , paragraphs
[0049] to
[0073] of Japanese Patent Application Laid-Open No. 2012-63387, paragraphs
[0016] to
[0018] of Japanese Patent Application Laid-Open No. 11-305036, paragraphs
[0009] to
[0011] of Japanese Patent Application Laid-Open No. 2001-133630, paragraphs
[0030] to
[0169] of Japanese Patent Application Laid-Open No. 2011-215337, paragraphs
[0021] to
[0075] of Japanese Patent Application Laid-Open No. 2010-106242, paragraphs
[0011] to
[0025] of Japanese Patent Application Laid-Open No. 2010-215846, paragraphs
[0017] to
[0069] of Japanese Patent Application Laid-Open No. 2011-048311, paragraphs
[0018] to
[0069] of Japanese Patent Application Laid-Open No. 2011- 213610, paragraphs
[0013] to
[0133] of Japanese Patent Application Publication No. 2011-237513, paragraphs
[0074] to
[0246] of Japanese Patent Application Publication No. 2016-006502, paragraphs
[0014] to
[0032] of Japanese Patent Application Publication No. 2018-053167, paragraphs
[0014] to
[0033] of Japanese Patent Application Publication No. 2020-11716, paragraphs
[0005] to
[0041] of International Publication No. 2016 / 060173, paragraphs
[0008] to
[0062] of International Publication No. 2016 / 136561, paragraphs
[0017] to
[0018] of International Publication No. 2017 / 154835 Paragraphs
[0014] to
[0033] , paragraphs
[0014] to
[0033] of International Publication No. 2017 / 154695, paragraphs
[0013] to
[0037] of International Publication No. 2017 / 195833, paragraphs
[0014] to
[0034] of International Publication No. 2018 / 164252, paragraphs
[0021] to
[0030] of International Publication No. 2018 / 186503, paragraphs
[0043] to
[0063] of International Publication No. 2019 / 189345, paragraphs
[0043] to
[0085] of International Publication No. 2019 / 225468, paragraphs
[0050] to
[0074] of International Publication No. 2020 / 004106,The substances described in paragraphs
[0015] to
[0038] of International Publication No. 2021 / 044843.
[0182] As the dichroic substance, a dichroic azo dye compound is preferred.
[0183] A dichroic azo dye compound refers to an azo dye compound whose absorbance varies according to the direction. A dichroic azo dye compound may or may not exhibit liquid crystallinity. In the case where a dichroic azo dye compound exhibits liquid crystallinity, any one of nematicity or smecticity may be exhibited. The temperature range for exhibiting a liquid crystal phase is preferably room temperature (about 20 to 28° C.) to 300° C., and is more preferably 50 to 200° C. from the viewpoint of operability and manufacturing applicability.
[0184] In the present invention, from the viewpoint of color tone adjustment, it is preferred to use at least one pigment compound (first dichroic azo pigment compound) having a maximum absorption wavelength in the wavelength range of 560 to 700 nm and at least one pigment compound (second dichroic azo pigment compound) having a maximum absorption wavelength in the wavelength range of greater than 455 nm and less than 560 nm.
[0185] In the present invention, three or more dichroic azo dye compounds may be used simultaneously. For example, from the viewpoint of making the light absorption anisotropic layer close to black, it is preferred to simultaneously use a first dichroic azo dye compound, a second dichroic azo dye compound, and at least one dye compound (third dichroic azo dye compound) having a maximum absorption wavelength in the range of greater than 380 nm and less than 455 nm.
[0186] In the present invention, the dichroic azo dye compound preferably has a crosslinkable group.
[0187] Examples of the crosslinkable group include a (meth)acryloyl group, an epoxy group, an oxetanyl group, and a styryl group. Among them, a (meth)acryloyl group is preferred.
[0188] The content of the dichroic substance is not particularly limited, but from the perspective of increasing the degree of orientation of the formed light absorption anisotropic layer, it is preferably 3% by mass or more, more preferably 8% by mass or more, and further preferably 10% by mass or more relative to the total mass of the light absorption anisotropic layer. The upper limit of the content of the dichroic substance is not particularly limited, but it is preferably 30% by mass or less, more preferably 29% by mass or less, and further preferably 25% by mass or less relative to the total mass of the light absorption anisotropic layer. In addition, when a plurality of dichroic substances are used simultaneously, the total amount of the plurality of dichroic substances is preferably within the above range.
[0189] Furthermore, the content of the dichroic substance is preferably 10 to 400 mg / cm2 in order to increase the degree of orientation of the formed light absorption anisotropic layer. 3 , more preferably 30 to 200 mg / cm 3 , more preferably 40 to 150 mg / cm 3 In addition, when a plurality of dichroic substances are used simultaneously, the total amount of the plurality of dichroic substances is preferably within the above range.
[0190] Here, the content of dichroic substances (mg / cm 3 ) can be obtained by measuring a solution obtained by dissolving an optical laminate having a light absorbing anisotropic layer or an extract obtained by immersing the optical laminate in a solvent using high-speed liquid chromatography (HPLC), but is not limited to the above method. In addition, quantification can be performed by using a dichroic substance contained in the light absorbing anisotropic layer as a standard sample.
[0191] As an example of a method for calculating the content of a dichroic substance, the following method can be cited: the volume is calculated by multiplying the thickness of the light absorption anisotropic layer obtained from a microscope observation image of a cross-section of the optical laminate and the area of the optical laminate used to measure the pigment amount, and the pigment amount measured by HPLC is divided by the volume to calculate the pigment content.
[0192] <Other ingredients>
[0193] In the present invention, the liquid crystal layer may contain, in addition to the above components, an adhesion improver, a surfactant, a plasticizer, a non-liquid crystal polymerizable compound, a polymer, and the like.
[0194] Here, as an example of the adhesion improver, there can be mentioned the reactive additives listed in paragraphs
[0123] to
[0129] of Japanese Patent Application Publication No. 2019-91088, the boric acid monomers listed in paragraphs
[0015] to
[0028] of International Publication No. 2015 / 053359, etc. The content is preferably 0.1% to 20% relative to the total mass of the solid component of the liquid crystal layer, more preferably 0.3% to 10.0%, and further preferably 0.5% to 5.0%.
[0195] Regarding surfactants, it is preferred to use compounds having a so-called leveling function that makes the applied film flat. For example, fluorine-containing compounds, silicon-containing compounds, or polyacrylate compounds can be used. Specifically, it is possible to use the compounds or additions described in the descriptions and embodiments of International Publication No. 2021 / 002333, International Publication No. 2022 / 014342, International Publication No. 2022 / 014340, Japanese Patent Publication No. 2020-98349,
[0031] to
[0033] , Japanese Patent Publication No. 2020-98349,
[0032] to
[0036] , International Publication No. 2023 / 054164, etc.
[0196] In particular, from the perspective of reducing environmental pollution, the surfactant is preferably a compound containing a silicon atom or a polyacrylate compound, preferably a compound having a branched siloxane structure. In particular, the copolymer (surfactant) described in [Table 1] of International Publication No. 2023 / 054164 is preferred. The content of the surfactant is preferably 0.01% to 10% relative to the total mass of the solid component of the liquid crystal layer, more preferably 0.01% to 6.0%, and further preferably 0.05% to 3.0%.
[0197] Similarly, from the viewpoint of reducing environmental pollution, the fluorine atom content of the surfactant is preferably low, preferably 10% or less, more preferably 5% or less, and further preferably 3% or less in terms of weight in the compound. As for the lower limit, 0% is most preferred, but a trace amount (e.g., 0.01 to 1.0%) may be contained within a range with little impact on environmental pollution.
[0198] The thickness of the liquid crystal layer is not particularly limited, but is preferably 0.1 to 10 μm, and more preferably 0.5 to 5 μm.
[0199] <Method for producing liquid crystal layer (light absorption anisotropic layer)>
[0200] The method for manufacturing a light-absorbing anisotropic layer is not particularly limited, but from the perspective of further improving the degree of orientation of the dichroic substance, a method preferably includes the following steps in sequence (hereinafter also referred to as the "present manufacturing method"): a step of coating a light-absorbing anisotropic layer-forming composition containing the above-mentioned liquid crystal compound and any dichroic substance and other components on the above-mentioned oriented film to form a coating film (hereinafter also referred to as the "coating film forming step") and a step of orienting the liquid crystal component contained in the above-mentioned coating film (hereinafter also referred to as the "orientation step").
[0201] The liquid crystal component is a component containing not only the above-mentioned liquid crystal compound but also a dichroic substance having liquid crystallinity.
[0202] Hereinafter, each step will be described.
[0203] The coating film forming step is a step of coating the above-mentioned light absorption anisotropic layer-forming composition on the alignment film to form a coating film.
[0204] By using a light-absorbing anisotropic layer-forming composition containing the above-mentioned solvent or a light-absorbing anisotropic layer-forming composition obtained by heating or the like to be melted into a liquid, the light-absorbing anisotropic layer-forming composition can be easily coated on the alignment film.
[0205] Examples of the coating method for the light absorption anisotropic layer-forming composition include known methods such as roll coating, gravure printing, spin coating, wire bar coating, extrusion coating, direct gravure coating, reverse gravure coating, die coating, spray coating, and inkjet.
[0206] The alignment step is a step of aligning the liquid crystal component (particularly, the dichroic substance) contained in the coating film. In the alignment step, it is considered that the dichroic substance is aligned along the liquid crystal compound aligned by the alignment film.
[0207] The orientation process may include a drying process. By drying, components such as solvents can be removed from the coating film. The drying process may be performed by leaving the coating film at room temperature for a predetermined time (e.g., natural drying), or by heating and / or blowing air.
[0208] The orientation step preferably includes a heat treatment, whereby the dichroic substance contained in the coating film is further oriented and the degree of orientation of the dichroic substance is further increased.
[0209] From the viewpoint of production suitability, the heat treatment is preferably performed at 10 to 250° C., more preferably 25 to 190° C. The heating time is preferably 1 to 300 seconds, more preferably 1 to 60 seconds.
[0210] The orientation process may include a cooling process performed after the heating process. The cooling process is a process of cooling the heated coating film to about room temperature (20 to 25° C.). As a result, the orientation of the dichroic substance contained in the coating film is further fixed and the orientation degree of the dichroic substance is further improved. There is no particular limitation on the cooling method, and it can be performed by a known method.
[0211] Through the above steps, a light absorption anisotropic layer can be obtained.
[0212] The present production method may include a step of curing the light-absorbing anisotropic layer after the alignment step (hereinafter also referred to as a “curing step”).
[0213] The curing step is performed, for example, by heating and / or light irradiation (exposure). Among them, the curing step is preferably performed by light irradiation.
[0214] As the light source for curing, various light sources such as infrared, visible light or ultraviolet light can be used, but ultraviolet light is preferred. In addition, ultraviolet light may be irradiated while heating during curing, or ultraviolet light may be irradiated through a filter that transmits only a specific wavelength.
[0215] Furthermore, the exposure may be performed in a nitrogen atmosphere. When the light absorption anisotropic layer is cured by radical polymerization, the inhibition of polymerization by oxygen is reduced, so the exposure is preferably performed in a nitrogen atmosphere.
[0216] [Protective layer]
[0217] The protective layer is also called a gas barrier layer and has a function of protecting the polarizing element of the present invention from gases such as oxygen in the atmosphere, moisture, or compounds contained in adjacent layers.
[0218] Regarding the oxygen barrier layer, for example, reference can be made to paragraphs
[0014] to
[0054] of Japanese Patent Publication No. 2014-159124, paragraphs
[0042] to
[0075] of Japanese Patent Publication No. 2017-121721, paragraphs
[0045] to
[0054] of Japanese Patent Publication No. 2017-115076, paragraphs
[0010] to
[0061] of Japanese Patent Publication No. 2012-213938, paragraphs
[0021] to
[0031] of Japanese Patent Publication No. 2005-169994, and paragraphs
[0122] to
[0132] of International Publication No. 2020 / 045216.
[0219] Furthermore, from the perspective of suppressing internal reflection, the protective layer also preferably contains an additive for adjusting the refractive index in order to reduce the refractive index difference with the liquid crystal layer. As preferred additives, reference can be made to paragraphs
[0110] to
[0112] of International Publication No. 2020 / 045216.
[0220] [Polarizing plate]
[0221] The polarizing plate of the present invention is a polarizing plate having the above-mentioned optical film of the present invention.
[0222] Here, when the liquid crystal layer included in the optical film of the present invention is not a light absorption anisotropic layer, the polarizing plate of the present invention includes a polarizer described later.
[0223] The polarizer of the present invention may also have other optical films or protective films described below, and other functional layers in addition to the optical film of the present invention described above. The function of the functional layer is not particularly limited, and for example, it may be a layer having functions such as a stress relaxation layer, a flattening layer, an antireflection layer, a refractive index adjustment layer, and an ultraviolet absorption layer.
[0224] The protective film may be sandwiched between the polarizers and used on both sides, or may be used on only one side of the polarizer.
[0225] When a protective film is provided on the same side as the optical film of the present invention, it is disposed between the polarizer and the optical film or on the side of the optical film opposite to the polarizer via a binder or an adhesive.
[0226] When the above-mentioned liquid crystal layer is a λ / 4 plate (positive A plate), the polarizing plate can be used as a circular polarizing plate.
[0227] 〔Polarizer〕
[0228] The polarizer is not particularly limited as long as it has a function of converting light into specific linearly polarized light, and a conventionally known absorption-type polarizer or reflection-type polarizer can be used.
[0229] As the absorption type polarizer, an iodine polarizer, a dye polarizer using a dichroic dye, a polyene polarizer, etc. can be used. Among the iodine polarizers and dye polarizers, there are coating type polarizers and stretching type polarizers, and both can be used. Preferably, a polarizer is made by adsorbing iodine or a dichroic dye on polyvinyl alcohol and stretching it.
[0230] Furthermore, as a method for obtaining a polarizer by stretching and dyeing a laminated film having a polyvinyl alcohol layer formed on a substrate, Japanese Patent No. 5048120, Japanese Patent No. 5143918, Japanese Patent No. 4691205, Japanese Patent No. 4751481 and Japanese Patent No. 4751486 can be cited, and known technologies related to these polarizers can also be preferably utilized.
[0231] As the coating type polarizer, WO2018 / 124198, WO2018 / 186503, WO2019 / 132020, WO2019 / 132018, WO2019 / 189345, Japanese Patent Application Publication No. 2019-197168, Japanese Patent Application Publication No. 2019-194685, and Japanese Patent Application Publication No. 2019-139222 can be mentioned, and known techniques related to these polarizers can also be preferably used.
[0232] As the reflective polarizer, a polarizer obtained by laminating different birefringent films, a wire grid polarizer, a polarizer obtained by combining cholesteric liquid crystal having a selective reflection region and a quarter wave plate, or the like can be used.
[0233] Among these, polyvinyl alcohol-based resins (containing -CH 2 -CHOH- as a repeating unit. In particular, a polarizer comprising at least one selected from the group consisting of polyvinyl alcohol and ethylene-vinyl alcohol copolymer.
[0234] Furthermore, from the viewpoint of imparting crack resistance, the polarizer may include a depolarizing portion along the opposing end sides. As the depolarizing portion, Japanese Patent Application Laid-Open No. 2014-240970 can be cited.
[0235] Furthermore, the polarizer may have a non-polarizing portion arranged at a predetermined interval in the longitudinal direction and / or the width direction. The non-polarizing portion is a partially decolorized decolorized portion. The configuration pattern of the non-polarizing portion can be appropriately set according to the purpose. For example, when the polarizer is cut (cut, punched, etc.) into a predetermined size in order to install it on an image display device of a predetermined size, the non-polarizing portion is arranged at a position corresponding to the camera portion of the image display device. As a configuration pattern of the non-polarizing portion, Japanese Patent Gazette No. 2016-27392 can be cited.
[0236] The thickness of the polarizer is not particularly limited, but is preferably 3 to 60 μm, more preferably 3 to 30 μm, and further preferably 3 to 10 μm.
[0237] 〔Protective film〕
[0238] The material of the protective film is not particularly limited, and examples thereof include cellulose acylate films (e.g., cellulose triacetate films, cellulose diacetate films, cellulose acetate butyrate films, cellulose acetate propionate films), polyacrylic resin films such as polymethyl methacrylate, polyolefins such as polyethylene and polypropylene, polyester resin films such as polyethylene terephthalate and polyethylene naphthalate, polyether sulfone films, polyurethane resin films, polyester films, polycarbonate films, polysulfone films, polyether films, polymethylpentene films, polyether ketone films, (meth) acrylonitrile films, polyolefins, polymers having an alicyclic structure (norbornene resins (ARTON: trade name, manufactured by JSR Corporation), amorphous polyolefins (ZEONEX: trade name, manufactured by Zeon Corporation)), etc. Among them, cellulose acylate films are preferred.
[0239] The optical properties of the protective film are not particularly limited, but when the protective film is provided on the same side as the optical film of the present invention, it is preferred that the following formula is satisfied.
[0240] 0nm≤Re(550)≤10nm
[0241] -40nm≤Rth(550)≤40nm
[0242] [Image display device]
[0243] The image display device of the present invention is an image display device including the optical film of the present invention or the polarizing plate of the present invention.
[0244] The display element used in the image display device is not particularly limited, and examples thereof include a liquid crystal cell, an organic electroluminescent (hereinafter referred to as "EL (Electro Luminescence)") display panel, and a plasma display panel, etc. Among these, a liquid crystal cell and an organic EL display panel are preferred, and a liquid crystal cell is more preferred.
[0245] That is, as the image display device, a liquid crystal display device using a liquid crystal cell as a display element or an organic EL display device using an organic EL display panel as a display element is preferable, and a liquid crystal display device is more preferable.
[0246] The image display device of the present invention is preferably a flexible panel.
[0247] Furthermore, as described above, the image display device of the present invention also includes an embodiment including the polarizing plate of the present invention, and thus may be a flexible panel including the polarizing plate of the present invention.
[0248] 〔Liquid crystal display device〕
[0249] A liquid crystal display device as an example of an image display device is a liquid crystal display device including the above-mentioned polarizing plate and a liquid crystal cell.
[0250] In addition, among the polarizing plates provided on both sides of the liquid crystal cell, it is preferable to use the above-mentioned polarizing plate as the polarizing plate on the front side, and it is more preferable to use the above-mentioned polarizing plate as the polarizing plates on the front side and the rear side.
[0251] Hereinafter, the liquid crystal cell constituting the liquid crystal display device will be described in detail.
[0252] <Liquid crystal unit>
[0253] The liquid crystal unit used in the liquid crystal display device is preferably VA (Vertical Alignment) mode, OCB (Optically Compensated Bend) mode, IPS (In-Plane-Switching) mode, FFS (Fringe-Field-Switching) mode or TN (Twisted Nematic) mode, but is not limited to these.
[0254] In a TN mode liquid crystal cell, rod-shaped liquid crystal molecules are substantially horizontally aligned when no voltage is applied, and further have a twisted alignment of 60 to 120°. TN mode liquid crystal cells are most commonly used as color TFT liquid crystal display devices and are described in many documents.
[0255] In a VA mode liquid crystal cell, rod-shaped liquid crystal molecules are substantially aligned vertically when no voltage is applied. VA mode liquid crystal cells include (1) a narrow VA mode liquid crystal cell in which rod-shaped liquid crystal molecules are substantially aligned vertically when no voltage is applied and are substantially aligned horizontally when a voltage is applied (described in Japanese Patent Laid-Open No. 2-176625), (2) a VA mode liquid crystal cell (described in SID97, Digest of tech. Papers 28 (1997) 845) in which a multi-domain VA mode is implemented to expand the viewing angle, (3) a liquid crystal cell in which rod-shaped liquid crystal molecules are substantially aligned vertically when no voltage is applied and are aligned in a twisted multi-domain orientation when a voltage is applied (described in Proceedings of the Japan Liquid Crystal Conference 58-59 (1998)), and (4) a SURVIVAL mode liquid crystal cell (published in LCD International 98). Furthermore, the VA mode heat-generating liquid crystal cell may be any one of PVA (Patterned Vertical Alignment), optical alignment, and PSA (Polymer-Sustained Alignment). Details of these modes are described in Japanese Patent Publication No. 2006-215326 and Japanese Patent Table No. 2008-538819.
[0256] Regarding the liquid crystal unit of the IPS mode, the rod-shaped liquid crystal molecules are substantially parallel to the substrate, and the liquid crystal molecules are planarly responsive by applying an electric field parallel to the substrate surface. Regarding the IPS mode, a black display is obtained when no electric field is applied, and the absorption axes of the upper and lower polarizers are orthogonal to each other. Japanese Patent Publication No. 10-54982, Japanese Patent Publication No. 11-202323, Japanese Patent Publication No. 9-292522, Japanese Patent Publication No. 11-133408, Japanese Patent Publication No. 11-305217, and Japanese Patent Publication No. 10-307291 disclose methods of using an optical compensation sheet to reduce light leakage during black display in an oblique direction and improve the viewing angle.
[0257] [Organic EL display device]
[0258] An organic EL display device as an example of an image display device includes, for example, a polarizer, a λ / 4 plate (positive A plate) composed of the above-mentioned liquid crystal cured layer, and an organic EL display panel in this order from the viewing side.
[0259] The organic EL display panel is a display panel composed of an organic EL element in which an organic light emitting layer (organic electroluminescent layer) is sandwiched between electrodes (cathode and anode). The structure of the organic EL display panel is not particularly limited, and a known structure can be adopted.
[0260] Example
[0261] Below, the present invention is further described in detail according to examples. The materials, usage, ratio, processing content, processing steps etc. shown in the following examples can be appropriately changed as long as they do not depart from the purport of the present invention. Therefore, the scope of the present invention should not be interpreted restrictively by the examples shown below.
[0262] [Example 1]
[0263] 〔Making of base material〕
[0264] The following composition was placed in a mixing tank, stirred, and then heated at 90°C for 10 minutes. The obtained composition was then filtered through a filter paper having an average pore size of 34 μm and a sintered metal filter having an average pore size of 10 μm to prepare a dope. The solid content concentration of the dope was 23.5% by mass, the amount of the plasticizer added was a ratio relative to the cellulose acylate, and the solvent of the dope was methylene chloride / methanol / butanol = 81 / 18 / 1 (mass ratio).
[0265]
[0266] [Chemical formula 3]
[0267]
[0268] [Chemical formula 4]
[0269]
[0270] The dope prepared above was cast using a roll film machine. The dope was cast from a mold so as to contact a metal support cooled to 0° C., and then the obtained web (film) was peeled off from the roll. The roll was made of SUS (stainless steel).
[0271] After the web (film) obtained by casting was peeled off from the drum, it was dried for 20 minutes in a tenter device at 30 to 40° C. using a clamp to hold both ends of the web while conveying the film. Subsequently, the web was post-dried by zone heating while being conveyed by rollers. The obtained web was knurled and then wound up to be a cellulose acylate film A1.
[0272] The obtained cellulose acylate film A1 had a film thickness of 60 μm, an in-plane retardation Re(550) of 1 nm at a wavelength of 550 nm, and a thickness-direction retardation Rth(550) of 35 nm at a wavelength of 550 nm.
[0273] [Formation of Photo-Alignment Film B1]
[0274] The photo-alignment film-forming composition B1 described later was continuously coated on the cellulose acylate film A1 by a wire bar. The support on which the coating film was formed was dried for 120 seconds with hot air at 140° C., and then the coating film was irradiated with polarized ultraviolet light (10 mJ / cm 2 The photo-alignment film B1 was formed using an ultra-high pressure mercury lamp to obtain a TAC (triacetyl cellulose) film with a photo-alignment film. The thickness of the photo-alignment film B1 was 1.5 μm.
[0275]
[0276]
[0277] Photo-alignment compound PA-1 (weight average molecular weight: 32000)
[0278] (In the formula, the numerical value described in each repeating unit represents the content (mass %) of each repeating unit relative to all repeating units.)
[0279] [Chemical formula 5]
[0280]
[0281] Thermal cationic polymerization initiator PAG-1
[0282] [Chemical formula 6]
[0283]
[0284] Stabilizer DIPEA
[0285] [Chemical formula 7]
[0286]
[0287] Polymer PA-2 (weight average molecular weight: 18000)
[0288] [Chemical formula 8]
[0289]
[0290] [Formation of light absorption anisotropic layer C1]
[0291] A light absorption anisotropic layer-forming composition C1 having the following composition was continuously applied on the obtained photo-alignment film B1 using a wire bar to form a coating film.
[0292] Next, the coating film was heated at 140°C for 15 seconds, then at 80°C for 5 seconds, and then cooled to room temperature (23°C). Next, the coating film was heated at 75°C for 60 seconds, and then cooled to room temperature again.
[0293] Then, irradiation was performed using an LED (light emitting diode) lamp (central wavelength: 365 nm) under irradiation conditions of 300 mJ, thereby forming a light absorption anisotropic layer C1 (polarizer) (thickness: 1.8 μm) on the photo-alignment film B1.
[0294] The transmittance of the light absorption anisotropic layer C1 in the wavelength region of 280 to 780 nm was measured using a spectrophotometer. As a result, the average visible light transmittance was 42%.
[0295] The absorption axis of the light absorption anisotropic layer C1 is located in the plane of the light absorption anisotropic layer C1 and is orthogonal to the width direction of the cellulose acylate film A1.
[0296]
[0297] Dichroic Material Dye-C1
[0298] [Chemical formula 9]
[0299]
[0300] Dichroic Material Dye-M1
[0301] [Chemical formula 10]
[0302]
[0303] Dichroic Material Dye-Y1
[0304] [Chemical formula 11]
[0305]
[0306] Liquid crystal compound L-1 (weight average molecular weight: 18000)
[0307] (In the following formula, the numerical values ("59", "15", "26") described in each repeating unit represent the content (mass %) of each repeating unit relative to all repeating units.)
[0308] [Chemical formula 12]
[0309]
[0310] Liquid crystal compound L-2 (a mixture of the following liquid crystal compounds (RA) (RB) (RC) in a ratio of 84:14:2 (mass ratio))
[0311] [Chemical formula 13]
[0312]
[0313] Adhesion Improver A-1
[0314] [Chemical formula 14]
[0315]
[0316] Surfactant F-1 (weight average molecular weight: 15000)
[0317] (In the formula, the numerical value described in each repeating unit represents the content (mass %) of each repeating unit relative to all repeating units. Also, Ac means -C(O)CH 3 . )
[0318] [Chemical formula 15]
[0319]
[0320] [Formation of protective layer D1]
[0321] A coating liquid D1 having the following composition was continuously applied onto the light absorption anisotropic layer C1 using a wire bar.
[0322] Then, it was dried with warm air at 80°C for 5 minutes and irradiated with an LED lamp (central wavelength 365nm) under irradiation conditions of 300mJ, thereby obtaining a laminated body having a protective layer D2 composed of polyvinyl alcohol (PVA) with a thickness of 0.6μm, that is, an optical film CP1 having a cellulose acylate film A1 (substrate), a photo-orientation film B1, a light absorption anisotropic layer C1 and a protective layer D1 adjacent to each other in sequence.
[0323]
[0324] Modified polyvinyl alcohol (weight average molecular weight: 14000)
[0325] [Chemical formula 16]
[0326]
[0327] Surfactant F-9
[0328] [Chemical formula 17]
[0329]
[0330] [Examples 2 to 14 and Comparative Examples 1 to 3]
[0331] An optical film was produced by the same method as in Example 1 except that various conditions such as the type and ratio (mass ratio relative to the total solid content) of the polymerizable polymer were changed as described in Table 3 below.
[0332] In addition, in the composition in which the composition of the photo-alignment film-forming composition was changed in Example 1, the total amount of the non-volatile components was made constant by adjusting the amount of EPICLON N-695 at the same time.
[0333] The structures of polymerizable polymers PA-3, PA-4, and PA-5 used in Comparative Example 3, Example 13, and Example 14 are shown below.
[0334] Polymer PA-3 (weight average molecular weight: 18000)
[0335] [Chemical formula 18]
[0336]
[0337] Polymer PA-4 (weight average molecular weight: 18000)
[0338] [Chemical formula 19]
[0339]
[0340] Polymer PA-5 (weight average molecular weight: 18000)
[0341] [Chemical formula 20]
[0342]
[0343] [Example 15]
[0344] [Formation of photo-alignment film B2]
[0345] The photo-alignment film-forming composition B2 described later was continuously coated on the cellulose acylate film A1 by a wire bar. The support on which the coating film was formed was dried for 120 seconds with warm air at 60° C., and then the coating film was irradiated with polarized ultraviolet light (100 mJ / cm 2 The photo-alignment film B2 was formed using an ultra-high pressure mercury lamp to obtain a TAC (triacetyl cellulose) film with a photo-alignment film. The thickness of the photo-alignment film B2 was 0.5 μm.
[0346]
[0347] Photo-aligned compound PA-6 (weight average molecular weight: 51000)
[0348] [Chemical formula 21]
[0349]
[0350] [Formation of light absorption anisotropic layer C2]
[0351] The composition C2 for forming a light absorption anisotropic layer of the following composition was continuously applied to the obtained photo-alignment film B2 by a wire rod to form a coating film. Then, the coating film was heated at 120°C for 60 seconds and cooled to room temperature. Then, an LED lamp (central wavelength 365nm) was used for irradiation under irradiation conditions of 300mJ, thereby forming a light absorption anisotropic layer C2 (polarizer) (thickness: 1.7μm) on the photo-alignment film B2, and an optical film CP2 having a cellulose acylate film A1 (substrate), a photo-alignment film B2 and a light absorption anisotropic layer C2 adjacent to each other in sequence was obtained.
[0352]
[0353] Dichroic substance Dye4
[0354] [Chemical formula 22]
[0355]
[0356] Dichroic substance Dye5
[0357] [Chemical formula 23]
[0358]
[0359] Dichroic substance Dye6
[0360] [Chemical formula 24]
[0361]
[0362] Dichroic substance Dye7
[0363] [Chemical formula 25]
[0364]
[0365] Liquid crystal compound M-1 (mixed at a ratio of Compound A / Compound B=75 / 25)
[0366] (Compound A)
[0367] [Chemical formula 26]
[0368]
[0369] (Compound B)
[0370] [Chemical formula 27]
[0371]
[0372] [Example 16]
[0373] The photo-alignment film used in Example 2 is referred to as photo-alignment film B3.
[0374] An optical film CP3 including the cellulose acylate film A1 (substrate), the photo-alignment film B3 and the light absorption anisotropic layer C2 adjacent to each other in this order was obtained.
[0375] [Example 17]
[0376] [Formation of photo-alignment film B4]
[0377] The photo-alignment film-forming composition B4 described later was continuously coated on the cellulose acylate film A1 by a wire bar. The support on which the coating film was formed was dried for 120 seconds with hot air at 140° C., and then the coating film was irradiated with polarized ultraviolet light (10 mJ / cm 2 The photo-alignment film B4 was formed using an ultra-high pressure mercury lamp to obtain a TAC (triacetyl cellulose) film with a photo-alignment film. The thickness of the photo-alignment film B4 was 1.5 μm.
[0378]
[0379]
[0380] [Formation of light absorption anisotropic layer C3]
[0381] A light absorption anisotropic layer-forming composition C3 having the following composition was continuously applied on the obtained photo-alignment film B4 using a wire bar to form a coating film.
[0382] Next, the coating film was heated at 140°C for 15 seconds, then heated at 80°C for 5 seconds, and then cooled to room temperature (23°C). Next, the coating film was heated at 75°C for 60 seconds and cooled to room temperature again. A light absorption anisotropic layer C3 (polarizer) (thickness: 3.5 μm) was formed on the photo-alignment film B4, and an optical film CP4 having a cellulose acylate film A1 (substrate), a photo-alignment film B4, and a light absorption anisotropic layer C3 adjacent to each other in this order was obtained.
[0383] The transmittance of the light absorption anisotropic layer C1 in the wavelength range of 280 to 780 nm was measured by a spectrophotometer. As a result, the average visible light transmittance was 75%.
[0384] The absorption axis of the light absorption anisotropic layer C3 is located out of the plane of the light absorption anisotropic layer C3.
[0385]
[0386] Orientation agent E-1
[0387] [Chemical formula 28]
[0388]
[0389] Orienting agent E-2
[0390] [Chemical formula 29]
[0391]
[0392] Surfactant F-2 (weight average molecular weight: 12000) (In the following formula, the numerical values ("80", "10", "10") described in each repeating unit represent the content (mass %) of each repeating unit relative to all repeating units.)
[0393] [Chemical formula 30]
[0394]
[0395] [Example 18]
[0396] [Formation of light absorption anisotropic layer C4]
[0397] A light absorption anisotropic layer-forming composition C4 having the following composition was continuously applied on the photo-alignment film B1 obtained by the same method as in Example 1 using a wire bar to form a coating film.
[0398] Next, the coating film was heated at 130° C. for 15 seconds, and then cooled to room temperature (23° C.) Next, the coating film was heated at 75° C. for 10 seconds, and then cooled to room temperature again.
[0399] Then, by irradiating with an LED lamp (central wavelength of 365 nm) under irradiation conditions of 300 mJ, a light absorption anisotropic layer C4 (polarizer) (thickness: 1.8 μm) was formed on the photo-alignment film B1, thereby producing an optical film.
[0400] The transmittance of the light absorption anisotropic layer C4 in the wavelength range of 380 to 780 nm was measured by a spectrophotometer. As a result, the average visible light transmittance was 42%.
[0401] The absorption axis of the light absorption anisotropic layer C4 is located within the plane of the light absorption anisotropic layer C4 and is orthogonal to the width direction of the cellulose acylate film A1.
[0402]
[0403] Dichroic Material Dye-C2
[0404] [Chemical formula 31]
[0405]
[0406] Dichroic Material Dye-Y2
[0407] [Chemical formula 32]
[0408]
[0409] Surfactant F-2 (weight average molecular weight: 15000)
[0410] (In the formula, the numerical value described in each repeating unit represents the content (mass %) of each repeating unit relative to all repeating units.)
[0411] [Chemical formula 33]
[0412]
[0413] [Example 19]
[0414] [Formation of light absorption anisotropic layer C5]
[0415] A light absorption anisotropic layer-forming composition C5 having the following composition was continuously applied on the photo-alignment film B1 obtained by the same method as in Example 1 using a wire bar to form a coating film.
[0416] Next, the coating film was heated at 130° C. for 15 seconds, and then cooled to room temperature (23° C.) Next, the coating film was heated at 75° C. for 10 seconds, and then cooled to room temperature again.
[0417] Then, by irradiating with an LED lamp (central wavelength of 365 nm) under irradiation conditions of 300 mJ, a light absorption anisotropic layer C5 (polarizer) (thickness: 1.8 μm) was formed on the photo-alignment film B1, thereby producing an optical film.
[0418] The transmittance of the light absorption anisotropic layer C5 in the wavelength range of 380 to 780 nm was measured by a spectrophotometer. As a result, the average transmittance of visible light was 42%.
[0419] The absorption axis of the light absorption anisotropic layer C5 is located in the plane of the light absorption anisotropic layer C5 and is orthogonal to the width direction of the cellulose acylate film A1.
[0420]
[0421]
[0422] Liquid crystal compound L-3
[0423] [Chemical formula 34]
[0424]
[0425] [Example 20]
[0426] [Formation of light absorption anisotropic layer C6]
[0427] A light absorption anisotropic layer-forming composition C6 having the following composition was continuously applied on the photo-alignment film B1 obtained by the same method as in Example 1 using a wire bar to form a coating film.
[0428] Next, the coating film was heated at 130° C. for 15 seconds, and then cooled to room temperature (23° C.) Next, the coating film was heated at 75° C. for 10 seconds, and then cooled to room temperature again.
[0429] Then, by irradiating with an LED lamp (central wavelength of 365 nm) under irradiation conditions of 300 mJ, a light absorption anisotropic layer C6 (polarizer) (thickness: 1.8 μm) was formed on the photo-alignment film B1, thereby producing an optical film.
[0430] The transmittance of the light absorption anisotropic layer C6 in the wavelength range of 380 to 780 nm was measured by a spectrophotometer. As a result, the average visible light transmittance was 42%.
[0431] The absorption axis of the light absorption anisotropic layer C6 is located in the plane of the light absorption anisotropic layer C6 and is orthogonal to the width direction of the cellulose acylate film A1.
[0432]
[0433]
[0434] Surfactant F-3 (weight average molecular weight: 11000)
[0435] (In the formula, the numerical value described in each repeating unit represents the content (mass %) of each repeating unit relative to all repeating units. Also, Ac means -C(O)CH 3 . )
[0436] [Chemical formula 35]
[0437]
[0438] [Example 21]
[0439] [Formation of the long polarizing film R1]
[0440] The cellulose acylate film A1 was continuously unwound at a speed of 20 m / min, and the above-mentioned photo-alignment film-forming composition B1 was applied using a slit die coater, and dried with warm air at 140°C for 120 seconds, thereby forming a photo-alignment film B1. At this time, the film thickness of the photo-alignment film B1 was 1.5 μm. Then, the photo-alignment film B1 was irradiated with polarized UV in a direction of 90° relative to the length direction of the film at an intensity of 8 mJ (313 nm basis) to impart an orientation restriction force, thereby forming a long strip photo-alignment film.
[0441] The above-mentioned composition C4 for forming anisotropic light absorption layer was applied to the obtained photo-alignment film B1 using a slit die coater, and the coating was heated at 130°C for 15 seconds, and then cooled to room temperature (23°C). Next, the coating was heated at 75°C for 10 seconds and cooled to room temperature again. Then, an LED lamp (central wavelength 365nm) was used for irradiation under irradiation conditions of 300mJ, thereby forming a light-absorbing anisotropic layer C4 (polarizer) (thickness: 1.8μm) on the photo-alignment film B1.
[0442] The transmittance of the light absorption anisotropic layer C4 in the wavelength range of 380 to 780 nm was measured by a spectrophotometer, and the average visible light transmittance was 42%. The absorption axis of the light absorption anisotropic layer C4 was located in the plane of the light absorption anisotropic layer C4 and parallel to the longitudinal direction of the cellulose acylate film A1.
[0443] The protective layer-forming coating liquid D1 was applied to the obtained optical anisotropic film C4 using a slit die coater, dried with warm air at 80°C for 5 minutes, and irradiated with an LED lamp (central wavelength 365nm) at 300mJ to form a protective layer D2 made of polyvinyl alcohol (PVA) with a thickness of 0.6μm. At this time, the thickness of the protective layer D2 was 0.6μm.
[0444] Then, the film was continuously wound into a roll, thereby obtaining a long polarizing film R1 as an optical film having an absorption axis in a direction parallel to the length thereof.
[0445] [Examples 22 and 23]
[0446] [Formation of Long Polarizing Films R2 and 3]
[0447] Long polarizing films R2 and 3 were prepared as optical films in the same manner as in Example 21 except that the composition and film thickness for forming the light absorption anisotropic layer were changed as described in the following Table 6. The composition used for forming the light absorption anisotropic layer is shown below.
[0448] [Light-absorption anisotropic layer-forming composition C7]
[0449]
[0450] [Light-absorption anisotropic layer-forming composition C8]
[0451]
[0452]
[0453] [Example 24]
[0454] [Formation of the long polarizing film R4]
[0455] The cellulose acylate film A1 was continuously unwound at a speed of 20 m / min, and the composition B1 for forming a photo-alignment film was applied using a slit die coater, and dried with warm air at 140°C for 120 seconds, thereby forming a photo-alignment film B1. At this time, the film thickness of the photo-alignment film B1 was 1.5 μm. Then, the photo-alignment film B1 was irradiated with polarized UV in a direction of 0° relative to the length direction of the film at an intensity of 8 mJ (313 nm basis) to impart an orientation restriction force, thereby forming a long strip photo-alignment film.
[0456] Using a slit die coater, the composition C4 for forming a light absorption anisotropic layer is applied to the obtained photo-alignment film, the coating is heated at 130°C for 15 seconds, and the coating is cooled to room temperature (23°C). Next, the coating is heated at 75°C for 10 seconds and cooled to room temperature again. Then, an LED lamp (central wavelength 365nm) is used to irradiate under irradiation conditions of 300mJ, thereby forming a light absorption anisotropic layer C4 (polarizer) (thickness: 1.8μm) on the photo-alignment film B1. The transmittance of the light absorption anisotropic layer C4 in the wavelength region of 380 to 780nm was measured by a spectrophotometer, and the result was that the average transmittance of visible light was 42%. The absorption axis of the light absorption anisotropic layer C4 is located in the plane of the light absorption anisotropic layer C4, perpendicular to the length direction of the cellulose acylate film A1.
[0457] Using a slit die coater, the coating liquid D1 for forming a protective layer was applied to the obtained optical anisotropic film C4, dried with warm air at 80°C for 5 minutes, and irradiated with an LED lamp (central wavelength 365nm) under irradiation conditions of 300mJ, thereby forming a protective layer D2 composed of polyvinyl alcohol (PVA) with a thickness of 0.6μm. At this time, the thickness of the protective layer D2 was 0.6μm. Then, it was continuously wound into a roll to obtain a long strip polarizing film R4 having an absorption axis in a direction perpendicular to the length as an optical film.
[0458] [Examples 25 and 26]
[0459] [Formation of Long Polarizing Films R5 and 6]
[0460] Long polarizing films R5 and 6 were produced as optical films by the same method as in Example 24 except that the composition for forming a light absorption anisotropic layer and the film thickness were changed as described in Table 6 below.
[0461] [evaluate]
[0462] 〔Peel force〕
[0463] The obtained optical film was used to evaluate the release force of the substrate.
[0464] Specifically, the optical film was cut into 150 mm×25 mm, and the surface of the optical film opposite to the substrate was fixed to a workbench using an Opteria D692 (thickness 15 μm) adhesive manufactured by LINTEC Corporation. The peeling force when the substrate was peeled off in a 180° direction at a speed of 5 m / min was measured under a 25°C environment using a digital dynamometer RZ-1 manufactured by AIKOH ENGINEERING Co., LTD. The results are shown in Tables 3 to 5 below.
[0465] 〔Orientation degree〕
[0466] The degree of orientation was evaluated using the obtained optical film.
[0467] Specifically, the transmittance of the light absorption anisotropic layer was measured using an automatic polarizing film measuring device (manufactured by JASCO Corporation, trade name VAP-7070), and the degree of orientation was calculated by the following formula. The results are shown in Tables 3 to 5 below.
[0468] Orientation degree: S = (Ax-Ay) / [2×Ay+Ax]
[0469] Ax: Absorbance when the incident polarized light and the polarizer of the evaluation sample are arranged in crossed Nicols
[0470] Ay: Absorbance when the incident polarized light and the polarizer of the evaluation sample are arranged in parallel Nicols
[0471] Ax=-log 10 (Tx / 100)
[0472] Ay=-log 10 (Ty / 100)
[0473] Tx: Transmittance when the incident polarized light and the polarizer of the evaluation sample are arranged in crossed Nicols (the incident polarized light is set to 100%)
[0474] Ty: Transmittance when the incident polarized light and the polarizer of the evaluation sample are arranged in parallel Nicols (the incident polarized light is set to 100%)
[0475] [Partiality]
[0476] The obtained optical film was evaluated using TOF-SIMS to determine the position where the secondary ion intensity derived from a specific compound showed a maximum value.
[0477] In addition, when analyzing the components in the depth direction of the optical film by TOF-SIMS while irradiating the ion beam, a series of operations were repeated, in which the components in the surface depth region of 1 to 2 nm were analyzed, and then the components in the next surface depth region of 1 to 2 nm were analyzed by digging 1 nm to several hundred nm in the depth direction. The positions showing the maximum value of the ion intensity were classified as follows. The results are shown in Tables 3 to 5 below.
[0478] A: The position of the maximum ionic intensity exists within 100nm from the support interface
[0479] B: The position of the maximum ionic intensity does not exist within 100 nm from the support interface
[0480]
[0481]
[0482]
[0483]
[0484] From the results shown in Tables 3 and 4, when the alignment film did not contain the specific compound, the peeling force of the substrate was high and it was difficult to peel the substrate (Comparative Example 1).
[0485] Furthermore, it is known that even when the alignment film contains a specific compound, if the specific compound is not biased on the substrate side, the substrate cannot be peeled off, or the peeling force of the substrate is high and it is difficult to peel off the substrate (Comparative Examples 2 and 3). In addition, in Comparative Example 2, the alignment film does not contain a thermal cationic polymerization initiator, so it is believed that when the light absorption anisotropic layer is coated on the alignment film, the alignment film is dissolved, eliminating the bias of the specific compound on the substrate side. In addition, in Comparative Example 3, the SP value difference between the substrate and the polymerizable polymer is large, so it is believed that the bias of the specific compound on the substrate side is reduced.
[0486] In contrast, the results shown in Tables 3 to 6 show that when the alignment film contains a specific compound and the specific compound is biased toward the substrate side, the peeling force between the substrate and the alignment film becomes appropriate, the substrate can be easily peeled off when peeling off the substrate, and the adhesion between the substrate and the alignment film can be fully ensured in operations other than peeling off the substrate (Examples 1 to 20). In addition, it was confirmed that the same performance can be obtained for a coil produced by continuous coating using a slot die coater (Examples 21 to 26).
[0487] From the comparison between Example 2 and Example 9, it can be seen that when the content of the specific compound is 0.2 to 20 mass % based on the mass of the alignment film, the degree of alignment of the liquid crystal layer is improved.
[0488] Furthermore, according to the comparison between Example 2 and Example 14, if the absolute value of the difference between the SP value of the polymerizable polymer and the SP value of the substrate is 1.7 MPa 1 / 2 Below, it is easy to adjust the peeling force of the substrate within the range of 0.05 to 0.35 N / 25 mm.
[0489] [Example 27]
[0490] [Formation of light absorption anisotropic layer C9]
[0491] An optical film was produced by the same method as in Example 20 except that the surfactant F-3 was changed to the following surfactant F-4 and the light absorption anisotropic layer C9 was formed instead of the light absorption anisotropic layer C6.
[0492] Surfactant F-4 (weight average molecular weight: 20000)
[0493] (In the formula, the numerical value described in each repeating unit represents the content (mass %) of each repeating unit relative to all repeating units.)
[0494] [Chemical formula 36]
[0495]
[0496] Next, the surfactant F-9 is changed to the following surfactant F-10. In addition, a protective layer D2 is formed on the light absorption anisotropic layer C9 by the same method as the formation of the protective layer D1 in Example 1, thereby obtaining an optical film CP27 having a cellulose acylate film A1 (substrate), a photo-orientation film B1, a light absorption anisotropic layer C9 and a protective layer D2 adjacent to each other in sequence.
[0497] Surfactant F-10
[0498] [Chemical formula 37]
[0499]
[0500] For the optical film CP27, the result of evaluating the partiality by the above-mentioned method is A. Similar to Example 20, the peeling force between the substrate and the oriented film becomes appropriate, the substrate can be easily peeled off, and the close contact between the substrate and the oriented film can be fully ensured during operations other than peeling the substrate.
Claims
1. An optical film comprising a substrate, an alignment film and a liquid crystal layer in this order, The alignment film contains at least one specific compound selected from the group consisting of a polymerizable macromolecule having a polymerizable group on a side chain and a polymer of the polymerizable macromolecule. While irradiating an ion beam from the surface of the orientation film on the liquid crystal layer side toward the surface on the substrate side, the secondary ion intensity of the specific compound in the orientation film is measured by time-of-flight secondary ion mass spectrometry, the maximum value of the secondary ion intensity originating from the specific compound exists in the region from the surface on the substrate side to the thickness position of 100 nm.
2. The optical film according to claim 1, wherein The specific compound is a polymer of the polymerizable high molecule.
3. The optical film according to claim 1, wherein The alignment film is a photo-alignment film.
4. The optical film according to claim 3, wherein: The photo-alignment film is an alignment film formed using an alignment film-forming composition containing the polymerizable polymer and a photo-alignment compound. The polymerizable polymer has a radical polymerizable group, and the photo-alignment compound has a cation polymerizable group.
5. The optical film according to claim 4, wherein: The alignment film-forming composition contains a polymerization initiator.
6. The optical film according to claim 5, wherein: The polymerization initiator is a photo-free radical polymerization initiator.
7. The optical film according to claim 1, wherein: The content of the specific compound is 0.2 to 20% by mass based on the mass of the alignment film.
8. The optical film according to claim 1, wherein: The liquid crystal layer contains a dichroic substance.
9. The optical film according to claim 1, wherein: The peeling force when the substrate is peeled off from the alignment film is 0.03 to 0.40 N / 25 mm.
10. The optical film according to claim 1, wherein The absolute value of the difference between the SP value of the polymerizable polymer and the SP value of the substrate is 1.7 MPa 1 / 2 the following.
11. The optical film according to claim 1, wherein: The weight average molecular weight of the polymerizable polymer is 5,000 to 100,000.
12. The optical film according to claim 1, wherein: The polymerizable group is an acryloyl group or a methacryloyl group. 13 . A polarizing plate comprising the optical film according to claim 1 . 14 . An image display device comprising the optical film according to claim 1 . 15 . An image display device comprising the polarizing plate according to claim 13 .
Citation Information
Patent Citations
Liquid crystal display device
JP1990176625A
Phase difference plate and liquid crystal device provided with the same
JP1997292522A
Liquid crystal display device
JP1998054982A
Horizontal electric field type liquid crystal display device
JP1999133408A
Liquid crystal display device and its manufacture
JP1999202323A
